If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 5) + 3x + (3x + -3) = 114 Reorder the terms: x + (5 + x) + 3x + (3x + -3) = 114 Remove parenthesis around (5 + x) x + 5 + x + 3x + (3x + -3) = 114 Reorder the terms: x + 5 + x + 3x + (-3 + 3x) = 114 Remove parenthesis around (-3 + 3x) x + 5 + x + 3x + -3 + 3x = 114 Reorder the terms: 5 + -3 + x + x + 3x + 3x = 114 Combine like terms: 5 + -3 = 2 2 + x + x + 3x + 3x = 114 Combine like terms: x + x = 2x 2 + 2x + 3x + 3x = 114 Combine like terms: 2x + 3x = 5x 2 + 5x + 3x = 114 Combine like terms: 5x + 3x = 8x 2 + 8x = 114 Solving 2 + 8x = 114 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 8x = 114 + -2 Combine like terms: 2 + -2 = 0 0 + 8x = 114 + -2 8x = 114 + -2 Combine like terms: 114 + -2 = 112 8x = 112 Divide each side by '8'. x = 14 Simplifying x = 14
| X^2-94x-7200=0 | | X^2-94x-720=0 | | 41.9x^2-45.9x+11.48=0 | | 6x+3=10+4x | | C=24+15d | | 20/35=21/x | | 2x/6=2 | | 3x+10=42-10x | | -15+b=-9 | | x*0.08=3 | | 3+v=8 | | 6(x+6)=8x+5-2x+31 | | 2sin^2(3x)+sinx-1=0 | | 45z=pz-v | | (2x-11)(-5-7)=0 | | 4.5=0.08x | | 8+2(4x-6)=6-5(2x+1) | | 1+2=2+3 | | 3xy-12xy+18x-2(xy+5x)= | | 6+2x=26+6x | | f(x)=2x^2-24x+73 | | 8xsquared-4x=0 | | 3xy-12xy+18x= | | -32n=-48 | | 6-2x=26+6x | | -3(2x-2)=-18 | | 8a+7a=5(a-8)+6(a+2) | | X+(X*.115)=2.89 | | -6+3(b-5)=8(-4b-7) | | -6+3(b-5)=8(-4-7) | | 2(X-1)/3-3(X-2)/2=1/4X-1 | | 190x-x^2+8625=0 |